2020
DOI: 10.1099/mgen.0.000350
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of global optrA-carrying Enterococcus faecalis uncovers a common chromosomal hotspot for optrA acquisition within a diversity of core and accessory genomes

Abstract: Linezolid-resistant Enterococcus faecalis (LREfs) carrying optrA are increasingly reported globally from multiple sources, but we lack a compre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 74 publications
(129 reference statements)
1
41
0
7
Order By: Relevance
“…Las variantes optrA -2, optrA -5 y opt r A -6 identificadas en este estudio han sido reportadas en humanos ( 4 , 7 , 8 , 14 , 21 ) y alimentos de origen animal ( 18 , 19 , 21 ); optrA -2 se ha identificado incluso en aguas residuales ( 18 , 21 ). En Colombia, optrA -2 se ha descrito previamente en carne cruda ( 16 , 21 ), mientras que es la primera vez que se reporta optrA 5 y optrA -6.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Las variantes optrA -2, optrA -5 y opt r A -6 identificadas en este estudio han sido reportadas en humanos ( 4 , 7 , 8 , 14 , 21 ) y alimentos de origen animal ( 18 , 19 , 21 ); optrA -2 se ha identificado incluso en aguas residuales ( 18 , 21 ). En Colombia, optrA -2 se ha descrito previamente en carne cruda ( 16 , 21 ), mientras que es la primera vez que se reporta optrA 5 y optrA -6.…”
Section: Discussionunclassified
“…Las variantes optrA -2, optrA -5 y opt r A -6 identificadas en este estudio han sido reportadas en humanos ( 4 , 7 , 8 , 14 , 21 ) y alimentos de origen animal ( 18 , 19 , 21 ); optrA -2 se ha identificado incluso en aguas residuales ( 18 , 21 ). En Colombia, optrA -2 se ha descrito previamente en carne cruda ( 16 , 21 ), mientras que es la primera vez que se reporta optrA 5 y optrA -6. La variante más común fue optrA -2 (EDM) y aunque ninguno de estos aislamientos presentó mecanismos adicionales de resistencia al linezolid, todos fueron resistentes al linezolid con CIM entre 8 y >256 µg/mL, contrastando con los datos publicados por Cai y cols ( 14 ) donde aislamientos optrA -2 (EDM) presentaron una CIM al linezolid en el rango sensible e intermedio (=2 y 4 µg/mL, respectivamente); el estudio de Cai y cols.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…We evaluated all 17 E. faecalis genomes for the presence of virulence-associated genes and operons using the VirulenceFinder database (33), along with manually searches for putative virulence gene sequences that have been previously described in E. faecalis (34) (Table S4). We found that fibronectin-binding proteins efbA and efaAfs, endocarditis and biofilm-associated pili ebpABC, sortase A (srtA), adhesin to collagen of E. faecalis (ace), general stress proteins gls24 and glsB, membrane metalloprotease associated with endocarditis (eep), thiol peroxidase for oxidative stress resistance (tpx), and sex pheromones cCF10, cOB1, cad and camE were present in the genomes of all isolates, with variable nucleotide identity (97-100% versus the reference sequence).…”
Section: Virulence-associated Gene Profiles and Biofilm Formationmentioning
confidence: 99%